The influence of cultivation technologies on the contamination of spring wheat crops and yield in the conditions of the Nizhny Novgorod region - A. V. Ivenin; V. V. Ivenin; Yu. A. Bogomolova; S. M. Golubev; I. I. Bugrov (Аграрная наука Евро-Северо-Востока, 2024)
The article presents the results of research of the influence of various cultivation technologies on the contamination of spring wheat crops and its yield for 2022–2023 in the conditions of the Nizhny Novgorod region on light gray loamy forest soil. There were studied the technologies various in methods of primary soil tillage (traditional, minimal – Mini-till, without tillage – No-till), and intensification level (basic, intensive). Spring wheat of the ʻZlataʼ cultivar was cultivated in the chain of rotation: clean fallow – peas - spring wheat. During the research period, it was established that the No-till technology contributed to an increase in the total contamination of spring wheat crops on an average for two years in the "tillering" phase (before herbicide treatment) to 36.2 pcs/m2 (84.7 % higher than the total contamination of wheat crops when cultivated using Mini-till technology and by 118.1 % –using traditional technology) and in the phase of "full grain ripeness" (before harvesting) up to 30.1 pcs/m2 (110.5 % higher than the total contamination of wheat crops cultivated using Mini-till technology and by 155.1 % according to traditional technology). It has been established that intensification of wheat production (application of mineral fertilizers in a dose of N70P50K50 before pre-sowing cultivation; using fungicide and herbicide in the "tillering" phase) results on average among studied technologies in decreasing the total contamination of crops during the "full grain ripeness" phase on average for two years up to15.7 pcs/m2 which is 38.2 % lower compared to the basic intensification degree of wheat cultivation technologies. It was found that the cultivation of spring wheat using traditional technology and Mini-till technology provides high yields: 3.09–3.43 t/ha, that is 0.63–0.96 t/ha higher than its yield when cultivated using No-till technology. There were no differences in the level of yield of spring wheat over the years of observation when cultivating it using traditional and Mini-till technologies. The intensification of spring wheat production makes it possible to increase the level of its yield for each of the studied technologies.